Pathogenesis, diagnosis, and management of dentin hypersensitivity - Alakkad, Tarik Mohammed Ali Al; Enezi, Asma Husain Al; Alazraqi, Marwan Saeed; Qurban, Abdulrahman Osama; Alhazmi, Lujain Saeed; Ballol, Khalid Mustafa; Madani, Slwan Mohammed Al; Almakrami, Mansour Hebah; Alomran, Ali Ahmed; Hakami, Rafaa Abdulsamad; Alqahtani, Sarah Saeed (International Journal Of Community Medicine And Public Health, 2023)
Dentin sensitivity is a problem characterized by brief sharp pain that occurs in response to things like changes in temperature, sweet or sour substances and mechanical factors. This condition significantly affects the lives of patients leading to restrictions and changes in oral hygiene routines. It is crucial for care to understand the causes, symptoms, diagnosis and management of dentin sensitivity. The development of dentin sensitivity is closely related to the structure of teeth which involves the exposure of tubes in the dentin that contain nerve endings sensitive to stimuli. Different theories, such as the theory and direct innervation theory provide insights into how this pain occurs. Diagnosis involves an evaluation of signs and symptoms along with patient history and specific tests to confirm sensitivity. Management options include adjusting behaviors using desensitizing toothpaste or fluoride applications utilizing bonding agents or even undergoing procedures like gingival grafts. These approaches aim to reduce pain and improve the quality of life for individuals affected by dentin sensitivity. Dental professionals play a role, in diagnosing, treating and educating patients about this condition to ensure results and better oral health.